BUILDING BLOCKS OF THE EARLIEST GOSPEL a road map to early Christian biography. - Bellinzoni, Arthur J. ([S.l.] : WIPF & STOCK PUBLISHERS, 2018)
This volume provides enough information about each story in the Gospel of Mark and about the gospel as a whole, in order to afford an informed understanding of the gospel. The evangelist was not writing a book for submission to a committee for inclusion in the Christian Bible. Rather, he was collecting existing oral and written tradition into a coherent narrative to promote, for his own Christian community, an understanding of the "good news" of Jesus the Messiah. The church to which the evangelist was writing, probably in Antioch of Syria, was likely already familiar with many of the stories from the church's evolving liturgy. Christians gathered in people's homes; there were no "churches" as we understand that word as a specific building for Christian worship. It was in such gatherings in homes that stories were told, perhaps as the basis for a message delivered by an elder of the church. Such stories illustrated some truth about Jesus or addressed an issue of importance to the church. In other words, these individual stories were developed to serve the needs of the Christian community. Historical accuracy was not a concern of the evangelist. Proclaiming Jesus as Messiah was his primary purpose.
Master record variable field(s) change: 050, 072, 082, 630
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books